The cost and impact of male circumcision on HIV/AIDS in Botswana - Bollinger, Lori A (The International AIDS Society, 2009)
The HIV/AIDS epidemic continues to be a major issue facing Botswana, with overall adult HIV prevalence estimated to be 25.7 percent in 2007. This paper estimates the cost and impact of the draft Ministry of Health male circumcision strategy using the UNAIDS/WHO Decision-Makers' Programme Planning Tool (DMPPT). Demographic data and HIV prevalence estimates from the recent National AIDS Coordinating Agency estimations are used as input to the DMPPT to estimate the impact of scaling-up male circumcision on the HIV/AIDS epidemic. These data are supplemented by programmatic information from the draft Botswana National Strategy for Safe Male Circumcision, including information on unit cost and program goals. Alternative scenarios were developed in consultation with stakeholders. Results suggest that scaling-up adult and neonatal circumcision to reach 80% coverage by 2012 would result in averting almost 70,000 new HIV infections through 2025, at a total net cost of US$47 million across that same period. This results in an average cost per HIV infection averted of US$689. Changing the target year to 2015 and the scale-up pattern to a linear pattern results in a more evenly-distributed number of MCs required, and averts approximately 60,000 new HIV infections through 2025. Other scenarios explored include the effect of risk compensation and the impact of increasing coverage of general prevention interventions. Scaling-up safe male circumcision has the potential to reduce the impact of HIV/AIDS in Botswana significantly; program design elements such as feasible patterns of scale-up and inclusion of counselling are important in evaluating the overall success of the program.